To study the factors considered on purchasing decision for residential property: a study on IOI Properties Berhad / Sharifah Haslinda Said Alwi - Said Alwi, Sharifah Haslinda (2013)
Fast-forward and five-and-a-half decades later, Malaysians today are better educated and enjoy higher standard of living. Malaysia has grown by leaps and bounds, yet some issues affecting the “Rakyat‟ remain to be solved. One of them is residential issue. This study is carried out to examine the factors attributes when purchasing a residential property and to determine if there is any association between Product in term of Residential Characteristic, Price, Location and Branding factor when purchasing the residential property. The title of this research is “To Study the Factors Considered on Purchasing Decision for Residential Property: A study on IOI Properties Berhad.”. The purpose of this research is to see the relationship between the variables. This study also attempts to improve the understanding of the customer satisfaction among the residents of IOI Properties Berhad‟s development property projects. This study has been conducted through literature study as well as questionnaire administered survey. Simple random sampling procedure has been used to determine sampling frame and size and a convenience sample of hundred respondents of different age groups, income and occupation have been considered for the survey. The collected data were analyzed to comply with the objectives and also to draw conclusions. In this research found that the independence variable which are Product, Price and Location are significant with the dependent variable which is Purchasing Decision. The most dominant factor is Price where influencing the purchasing decision on residential property.